Peran ICT bagi Organisasi Media Massa dan Budaya Masyarakat - MUTIA RAHMI PRATIWI (Universitas Muhammadiyah Yogyakarta, 2014)
Humans have a need to communicate and obtain information from various sources. However, the distance and time limitations become a significant obstacle in communicating and obtaining information. ICT development which is the development of information, communication, and technology has given a significant impact towards mass media organizations and the society in both cultural and social aspects. ICT development is able to facilitate people to access information anywhere, anytime and any information that they need without significant limitation. Keywords: ICT, Mass Media and society